"APPLICATION OF INNOVATIVE TECHNOLOGIES IN THE MANAGEMENT OF THE POMEGRANATE FRUIT MOTH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article highlights the biological characteristics of the pomegranate fruit moth (Euzophera punicaella Mooz), the damage it causes, as well as traditional and advanced methods of control. Information is provided on the advantages of pheromone technologies, biological agents, and integrated protection systems. Research results indicate that the use of advanced technologies not only increases productivity but also ensures ecological safety.